Analysis for Science Librarians of the 2018 Nobel Prize in Physiology or Medicine: The Life and Work of James P. Allison and Tasuku Honjo. Issue 1 (2nd January 2019) - Gilman, Neyda V.
ABSTRACT: On October 1, 2018, James P. Allison and Tasuku Honjo were awarded the 2018 Physiology or Medicine Nobel for their work leading to Immune Checkpoint Inhibition (ICI). ICI is the fourth pillar of cancer treatment and has been used to treat previously un-treatable cancers. Allison discovered that the protein CTLA-4 acts as a T cell brake while Honjo discovered another T cell brake, PD-1. Releasing these brakes allows the immune system to attack tumors, sometimes leading to complete elimination. While there is still more research to be done, Allison's and Honjo's work is a breakthrough in cancer immunotherapy.